2019
DOI: 10.7556/jaoa.2019.090
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Osteopathic Medical Students’ Personal Health on Attitudes Toward Counseling Obese Pediatric Patients

Abstract: Context: Research has shown that physicians with positive health and lifestyle behaviors have more positive attitudes toward effective counseling, but little is known about how personal health behaviors of medical students influence their attitudes regarding pediatric obesity counseling before entering practice. Objective: To determine whether the personal health status and habits of osteopathic medical students influence their attitudes toward counseling obese pediatric patients regarding lifestyle behaviors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…17 We reviewed 2 studies that found an association between medical students' fruit and vegetable intake and their attitudes towards providing patient nutritional counseling. 5,8 Specifically, Duperly et al found 5th-year Colombian medical students who consumed 5 or more daily servings of fruits and vegetables were more likely to agree or strongly agree that it is important for physicians to counsel patients on this behavior. 5 Whipps et al found that osteopathic students in Ohio who ate 3 or more vegetables per day and 2 or more fruits per day had higher pediatric dietary counseling scores (including agreeing with ''physicians have a responsibility to promote eating a healthy diet with their patients'') compared with students who had lower levels of vegetable and/or fruit intake.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…17 We reviewed 2 studies that found an association between medical students' fruit and vegetable intake and their attitudes towards providing patient nutritional counseling. 5,8 Specifically, Duperly et al found 5th-year Colombian medical students who consumed 5 or more daily servings of fruits and vegetables were more likely to agree or strongly agree that it is important for physicians to counsel patients on this behavior. 5 Whipps et al found that osteopathic students in Ohio who ate 3 or more vegetables per day and 2 or more fruits per day had higher pediatric dietary counseling scores (including agreeing with ''physicians have a responsibility to promote eating a healthy diet with their patients'') compared with students who had lower levels of vegetable and/or fruit intake.…”
Section: Discussionmentioning
confidence: 99%
“…5 Whipps et al found that osteopathic students in Ohio who ate 3 or more vegetables per day and 2 or more fruits per day had higher pediatric dietary counseling scores (including agreeing with ''physicians have a responsibility to promote eating a healthy diet with their patients'') compared with students who had lower levels of vegetable and/or fruit intake. 8 Specific to chiropractic students, DuMonthier et al found students with vegetarian diets (compared to students who reported heavy meat consumption) were more likely to rate as important that chiropractors educate patients on healthy behaviors and to model healthy behaviors. 9 In 14% of our reviewed files, students reported meeting fruit and vegetable dietary guidelines at the beginning of the DCP, which is similar to the 15% of Ohio osteopathic students meeting these guidelines in a 2019 study by Whipps et al 8 and higher than the 10% reported by California pharmacy and medical students in the study by Bergeron et al 14 By the end of our DCP, 30% of our students reported meeting these guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations